Carapace length and exoskeleton weight help predict chitin yield of giant freshwater prawn (Macrobrachium rosenbergii) cultured in perennial reservoirs across different agroecological zones in Sri Lanka - Sanuja, R.G.; Jayasinghe, A.D.; Deepananda, K.H.M.A. (Australian Center of International Agricultural Research, 2026)
Chitin, the second most abundant polysaccharide, is found in the exoskeletons of crustaceans, including the GFP (M. rosenbergii), which is an important commodity in CBF in Sri Lanka. We examine the chitin yield of GFP inhabiting perennial reservoirs (n=25) scattered across different agroecological zones (n=6) in Sri Lanka, as well as the relationships between chitin biomass from GFP exuviae and morphometric characteristics (GFP length) and yield characteristics (exoskeleton weight) of GFP collected from various agroecological zones. The discarded inedible exoskeletons of GFP are used to extract chitin through a process that includes preconditioning, demineralisation and deproteinisation. The chitin yields significantly differ (p<0.05) among GFP-inhabiting reservoirs across agroecological zones. The highest biometric characteristics of GFP are observed in reservoirs with annual rainfall of 900 mm or less, which may enhance the production of GFP through CBF in Sri Lanka. The highest chitin yield (18.30±5.24%) was obtained from GFP exoskeletons inhabiting reservoirs with 900 mm of annual rainfall. Strong correlations were observed between chitin yields and carapace length, as well as the shell weight of GFP inhabiting reservoirs across the 3 derived agroecological zones. The results support the hypothesis that the agroecological status of reservoirs influences the quantity of chitin extracted from the exoskeletons of GFP. Thus, the study concludes that the chitin yield of GFP can be predicted using either carapace length or exoskeleton weight, which could assist in establishing a small-scale chitin production industry in Sri Lanka.
Keywords: Culture-based fisheries; Agroecological zones; Relationship; Predicting; Chitin